2012
DOI: 10.1161/circinterventions.112.975862
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Impact of Risk Factor Control in Patients With Stable Claudication Presenting for Peripheral Vascular Interventions

Abstract: Background— Peripheral arterial disease is a manifestation of systemic atherosclerosis and is predictive of future cardiovascular events. Clinical trial data have demonstrated that medical therapy can attenuate cardiovascular morbidity and mortality in patients with peripheral arterial disease. The utilization and impact of recommended medical therapy in a contemporary population of patients who undergo percutaneous interventions for lifestyle-limiting peripheral arterial disease is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…We have previously shown that prescription of EBMT prior to percutaneous revascularization is associated with fewer peripheral vascular events at 6 months, including fewer repeat PVI procedures. 15 Programs such as the American College of Cardiology's Guidelines Applied in Practice (GAP) project and Get with the Guidelines (GWTG) program have been shown to improve adherence to EBMT in CAD patients. The GAP project is a multifaceted intervention that created systems and guideline-based tools to increase adherence to EBMT for patients with an acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that prescription of EBMT prior to percutaneous revascularization is associated with fewer peripheral vascular events at 6 months, including fewer repeat PVI procedures. 15 Programs such as the American College of Cardiology's Guidelines Applied in Practice (GAP) project and Get with the Guidelines (GWTG) program have been shown to improve adherence to EBMT in CAD patients. The GAP project is a multifaceted intervention that created systems and guideline-based tools to increase adherence to EBMT for patients with an acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…13 The use of risk factor modification in patients with symptomatic PAD who undergo LER is also low. 8,11,18 Conte and colleagues examined the medical therapy provided to 1403 patients who underwent infrainguinal bypass for critical limb ischemia as part of the PREVENT III trial. 8 On admission, 67% were taking an antiplatelet and 46% a lipid-lowering agent.…”
Section: Discussionmentioning
confidence: 99%
“…Ardati and colleagues found that users of aspirin and statins had decreased peripheral intervention, limb salvage surgery, and amputation at six months, but no difference in death, myocardial infarction, and stroke. 11 Patients in that study were treated for claudication and followed for a relatively short duration. Armstrong and colleagues reported that PAD patients with claudication (44%) or critical limb ischemia (56%) who underwent angiography and met all four guideline-based therapies experienced decreased major adverse events compared with patients who receive fewer than four recommended therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При анализе факторов, ассоциированных с приемом комбинированной терапии, таковыми оказались: наличие сопутствующей ИБС, сахар-ного диабета, предшествующая реваскуляризация по поводу ОЗАНК [4,15] и число факторов риска не менее трех [4]. Напротив, наличие критической ише-мии нижних конечностей не влияло на частоту назна-чения кардиоваскулярной протективной терапии [4], что согласуется с нашими данными -группы с раз-личной выраженностью ОЗАНК не различались по частоте назначения препаратов.…”
Section: результатыunclassified